2022
DOI: 10.1172/jci.insight.156559
|View full text |Cite
|
Sign up to set email alerts
|

In-depth analysis of SARS-CoV-2–specific T cells reveals diverse differentiation hierarchies in vaccinated individuals

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines pose as the most effective approach for mitigating COVID-19 pandemic. High-degree efficacy of SARS-CoV-2 vaccines in clinical trials indicate that vaccination invariably induces an adaptive immune response. However, the emergence of breakthrough infections in vaccinated individuals suggest that the breadth and magnitude vaccine-induced adaptive immune response may varies. We assessed vaccine-induced SARS-CoV-2 Tcell response in twenty-one va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…In addition, the lack of difference in T cells specific for spike peptides between vaccinated and unvaccinated patients may reflect limitations of the vaccines to induce T cell responses. The detection of SARS-CoV-2-specific CD8 T cells was restricted to two immunocompromised patients with high CD8 T cell counts and two immunocompetent patients that had been vaccinated, which is in line with previous findings illustrating that COVID-19 vaccination elicits CD4 T cell dominant immune responses [ 33 ]. Memory T cells rapidly express effector activity after antigen recognition presented by non-professional antigen presenting cells.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the lack of difference in T cells specific for spike peptides between vaccinated and unvaccinated patients may reflect limitations of the vaccines to induce T cell responses. The detection of SARS-CoV-2-specific CD8 T cells was restricted to two immunocompromised patients with high CD8 T cell counts and two immunocompetent patients that had been vaccinated, which is in line with previous findings illustrating that COVID-19 vaccination elicits CD4 T cell dominant immune responses [ 33 ]. Memory T cells rapidly express effector activity after antigen recognition presented by non-professional antigen presenting cells.…”
Section: Discussionsupporting
confidence: 90%
“…This cellular response was independent of the serological status as T‐cell responses were elicited in the absence or presence of circulating antibodies, consistent with a non‐redundant role as key determinants of immune protection against COVID‐19 26 . This contribution of a T‐cellular response to vaccination might implement the compromised humoral immunity protection against various current and emerging SARS‐CoV‐2 variants 49 …”
Section: Discussionmentioning
confidence: 55%
“…26 This contribution of a T-cellular response to vaccination might implement the compromised humoral immunity protection against various current and emerging SARS-CoV-2 variants. 49 This study showed that CLL-directed treatments influenced the magnitude of spike-specific T-cell responses to vaccine. Analysis on CLL treatment subgroups revealed a significantly higher production of IFNγ and TNFα by CD4 + T cells in patients under a BTK inhibitor compared to other treatments, while cytokine levels in CD8 + T cells were not influenced by CLL treatment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[81][82][83] The assessment of cytokine production in response to the peptide pool would allow assumptions with regard to the T-cell (poly-) functionality. 28,84,85 Most importantly, the assessment of cellular immunity towards SARS-CoV-2 using these peptides in combination with the antibody status could provide a better understanding of the adaptive immune response and facilitate more refined public health interventions. 86 Other groups could show that the T-cell and antibody responses against SARS-CoV-2 spike glycoprotein remain effective against the currently dominating B.1.1.529 VoC.…”
Section: Discussionmentioning
confidence: 99%